2020
DOI: 10.1111/jcmm.14830
|View full text |Cite
|
Sign up to set email alerts
|

Identification of immune‐enhanced molecular subtype associated with BRCA1 mutations, immune checkpoints and clinical outcome in ovarian carcinoma

Abstract: Ovarian carcinoma has the highest mortality among the malignant tumours in gynaecology, and new treatment strategies are urgently needed to improve the clinical status of ovarian carcinoma patients. The Cancer Genome Atlas (TCGA) cohort were performed to explore the immune function of the internal environment of tumours and its clinical correlation with ovarian carcinoma. Finally, four molecular subtypes were obtained based on the global immune‐related genes. The correlation analysis and clinical characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 37 publications
(62 reference statements)
4
38
0
Order By: Relevance
“…A study divided triple-negative breast cancer into three subgroups based on immune profiling [ 83 ]: the immunity-high group had the most HLA genes with higher expression, the immunity-mid had medium expression, and the immunity-low group had HLA genes with lower expression. Similarly, the immunity-high group also had high MIC class I, Type I IFN response, Type II IFN response, and APC [ 29 , 83 , 84 ]. However, the immunity-low group had MIC class I and APC with a lower expression [ 29 , 83 , 84 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A study divided triple-negative breast cancer into three subgroups based on immune profiling [ 83 ]: the immunity-high group had the most HLA genes with higher expression, the immunity-mid had medium expression, and the immunity-low group had HLA genes with lower expression. Similarly, the immunity-high group also had high MIC class I, Type I IFN response, Type II IFN response, and APC [ 29 , 83 , 84 ]. However, the immunity-low group had MIC class I and APC with a lower expression [ 29 , 83 , 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the immunity-high group also had high MIC class I, Type I IFN response, Type II IFN response, and APC [ 29 , 83 , 84 ]. However, the immunity-low group had MIC class I and APC with a lower expression [ 29 , 83 , 84 ]. In the present study, as shown in Figure 5 , we found the same as the above studies.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations